Chemotaxonomic Studies On Psychotria Rostrata And Alseodaphne Perakensis - Mahmud, Zurina (1989)

(untitled)
A chemotaxonomic investigation on the basic fraction of a medicinal plant Psycrotria rostrata, has resulted in the isolation of six alkaloidal components . The structures of these alkaloids were elucidated using spectroscopic methods such as UV, IR, NMR, MS and also by comparison with literature . The alkaloids were found to be chimonanthine , calycanthine, hodgkinsine , a stereoisomer of quadrigemine B, designated as Z-2 and two new compounds, Z-3 and Z-4. All these alkaloids were actually oligamers of either two , three or four units of compounds derived from tryptamines . Chimonanthine , hodgkinsine , Z-2 and Z-4 were made up of pyrrolidinoindoline type structures While calycanthine was a